Synthesis and application of an N-acylated L-homoserine lactone derivatized affinity matrix for the isolation of quorum sensing signal receptors - Praneenararat, Thanit (2011)
The design and synthesis of an agarose resin functionalized with a Gram-negative quorum sensing (QS) signaling molecule analogue is described. The modified resin was utilized in affinity pull-down assays to successfully isolate QscR, a LuxR-type QS receptor from Pseudomonas aeruginosa. This resin may facilitate the identification of novel QS signal receptors using affinity chromatography techniques.